Orientation entrepreneurship and neighborhood industry to formation strategy commerce on performance commerce textile in java west, Indonesia - Suparman, Aman (2024)
The existence of the textile industry in Indonesia can absorb a large number of workers and is able to encourage the establishment of other supporting industries. However, despite its importance, not much has been done to investigate the factors affecting the performance of PKS Tekstil in West Java, particularly the role of the entrepreneurial orientation variable, the external environment and the business strategy. This study was conducted to investigate the factors that influence commercial performance, in particular the role of entrepreneurial orientation variables (encompassing innovation, proactive and risk-taking) and the outcome environment and trade strategy (encompassing differentiation, focus and cost advantages). This study examines the relationship between entrepreneurial orientation and commercial strategy, the relationship between external concerns and commercial strategies, and the relationship between business strategies and commercial performance. In addition, this study also looks at the mediation of the commercial strategy on the relationship between entrepreneurial orientation and commercial achievement, and the mediation impression of the commercial strategy on the relationship between the external environment and the business achievement. The data collection method used a questionnaire. The number of samples in this study were 384 PKS Textiles in West Java covering the areas of Bandung City, Cimahi City, Cirebon City, Tasikmalaya City, Bandung Regency and West Bandung Regency. Partial Least Square Structural Equation Modeling (PLS-SEM) method was used to analyze the data of this study. The results of the study suggest that entrepreneurial orientation (encompassing innovation and proactive dimensions) has a positive and significant relationship to the commercial strategy partially. However, the risk-taking dimension of entrepreneurial orientation does not have a significant relationship with the commercial strategy. The output shortness variable has a positive and significant relationship with the commercial strategy (summarizing the dimensions of focus and cost advantage). However, the external environment has no relationship with the differentiation dimension of the commercial strategy. Furthermore, the variable business strategy has a positive and significant relationship with business achievement. Finally, the findings of this study explain that the variable business strategy mediates the relationship between entrepreneurial orientation (encompassing innovation and proactivity) and commercial achievement. However, the variable business strategy did not mediate the relationship between risk taking from entrepreneurial orientation and commercial performance. Likewise, the variable business strategy (encapsulating the dimensions of focus and cost advantage) mediates the relationship between the outcome environment and commercial achievement. However, the definition dimension of the commercial strategy does not mediate the relationship between the external environment and the commercial performance. This study contributes to the literature by showing the influence of entrepreneurial orientation, output environment and commercial strategy on commercial performance in the context of PKS Tekstil in West Java. PKS Tekstil in West Java is expected to be able to take the opportunities and opportunities that exist so that better commercial achievements can be achieved, PKS leaders need to increase the range of resources they have to be mobilized to achieve the expected commercial achievements.